A comparative study for the design of rectangular and circular isolated footings using new models (2016)
This paper presents a comparative study for design of reinforced concrete isolated footings of rectangular and circular form subjected to axial load and bending moments in two directions using new modelsto obtain the most economical footing. The new models consider the real soil pressure acting on contact surface of the footing and this pressure is different in all contact area, with a linear variation, this pressure is presented in terms of the axial load, the larger moment around the “X” axis and the smaller moment around the “Y” axis, where the centroidal axes are “X” and “Y” of the footing. The main part of this research is to show the differences of the two models. Results show that the circular footings are more economical with respect to the rectangular footings. Therefore, the new model for design of circular isolated footings should be used, and complies with the real conditions.